Code-Switching in the Letters of Vilnius University Professors at the End of the 18th century - Girininkaitė, Veronika (Taikomoji kalbotyra, 2020)
In order to show how research on historical epistolary language can contribute to sociolinguistics and applied linguistics, the present article examines some examples of late 18th-century letters. The research sample includes letters written to Vilnius University professors in that period (now archived in the Vilnius University Library), where the authors of the letters use code-switching or write in a language other than what we would nowadays think of as default. The cases under investigation have revealed that the use of an unusual language could be motivated by pedagogical goals, whereas code-switching could be caused, among other factors, by the need to refer to new realities or to clarify meaning; it could also be used for rhetorical expression (poetic function of language). The article is also important in that it presents accidentally detected instances of code-switching that are generally hard to identify in historically distant letters, e.g. Polish elements in French, Lithuanian and Russian elements in Polish texts. The article is intended to stimulate interest in the research on archaic manuscripts and to enrich the existing knowledge about the linguistic environment of the old Vilnius University.